Situation Report: Yugoslavia, 11 February 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Young Yugoslavs Disenchanted with the Regime / by Slobodan Stankovic Article Condemns Persecution of Intellectuals / by Slobodan Stankovic Tito's Works Attributed to Ghostwriters / by Slobodan Stankovic Joint Ventures / by Slobodan Stankovic Gypsies to Get Their Own Television Program / by Slobodan Stankovic